Preparation and application of aqueous zinc ion battery electrolyte containing trace tri-n-octylphosphine oxide additive

By using tri-n-octylphosphine as an electrolyte additive in aqueous zinc ion batteries, a zinc-philic hydrophobic layer and a hydrogen bond network are destroyed, the problems of dendrites are solved, and the cycle life and stability of the battery are significantly improved. sex.

CN119230976APending Publication Date: 2024-12-31ANHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523079.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the circulation process, aqueous zinc ion batteries have problems such as disordered growth, corrosion and hydrogen evolution, which affects their cycle life and stability and hinders their large-scale development.

Method used

A trace amount of trin-n-octylphosphine is used as an electrolyte additive to form a zinc-philic hydrophobic layer through its adsorption on the surface of the zinc anode, destroying the hydrogen bond network, regulating the deposition process of zinc ions, and reducing the generation of side reactions.

Benefits of technology

It significantly improves the stability and reversibility of the zinc anode, extends the cycle life of the aqueous zinc ion battery, inhibits corrosion and dendrite growth, and improves the cycle stability and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230976A_ABST
    Figure CN119230976A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of an aqueous zinc ion battery electrolyte containing a trace amount of tri-n-octylphosphine oxide (TOPO) additive. A main research method comprises the step of adding a mixed organic compound additive of the trace amount of tri-n-octylphosphine oxide and a proper amount of a methanol cosolvent into a zinc trifluoromethanesulfonate (Zn (OTF) 2) electrolyte of an aqueous zinc ion battery. The additive not only is environment-friendly and remarkable in effect of prolonging the cycle life, but also is low in cost, so that the additive has a good application prospect. Along with the addition of the electrolyte additive, the activity of free water in the electrolyte can be limited, and a hydrogen bond network among water molecules is destroyed, so that the hydrogen evolution reaction of a zinc anode is effectively inhibited; a zinc-loving hydrophobic layer is formed on the surface of the anode, so that the electrochemical deposition behavior of zinc ions in a zinc trifluoromethanesulfonate electrolyte can be obviously improved, the zinc ions are induced to be uniformly and compactly deposited on the zinc anode interface of the battery, the formation of zinc dendrites is inhibited, and the inherent corrosion problem of the anode is greatly improved; and the problem of capacity fading in the whole battery circulation process is solved to a certain extent. And a certain promotion effect is achieved for development and subsequent research of the aqueous zinc ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to the field of aqueous zinc ion battery electrolyte additives Background Art

[0002] With the increasing depletion of fossil energy such as oil, it is particularly important to develop new environmentally friendly renewable energy. However, due to the intermittent nature of renewable energy supply, efficient, safe and low-cost energy storage technology is needed to support it. Among them, aqueous zinc-ion batteries stand out in energy storage devices with their safety, environmental protection, low cost and large theoretical capacity. They have broad application prospects, but at the same time, aqueous zinc-ion batteries also have some challenges. For example, the disordered growth of anode dendrites, corrosion and hydrogen evolution have affected the cycle life of aqueous zinc-ion batteries, thus hindering the large-scale development of aqueous zinc-ion batteries.

[0003] In recent years, people have been committed to the research of inhibiting dendrite growth and side reactions, which mainly include the adjustment of anode structure, the construction of negative electrode surface coating, the regulation of electrolyte additives and the modification of diaphragms. The electrolyte additive research strategy has been widely studied due to its convenient operation and significant effect. Compared with the artificial coating constructed on the zinc surface through complex preparation processes, due to the instability of the binder performance, the coating may fall off during the electroplating cycle, thus affecting the battery performance. The electrolyte additive can regulate the deposition process of zinc ions by adsorbing on its surface to form a multifunctional layer, changing the solvation sheath structure of zinc ions and reducing the occurrence of side reactions. Therefore, it is very important to design an electrolyte additive that regulates the desolvation of zinc ions and induces uniform deposition of zinc ions. Summary of the invention

[0004] In view of the above-described shortcomings, the present invention provides a preparation and application of an aqueous zinc ion battery electrolyte containing a trace amount of tri-n-octylphosphine oxide additive. Since the solubility of tri-n-octylphosphine oxide in the present invention is not high in water, an appropriate amount of methanol is added as a cosolvent to help it dissolve in water. Only a very small amount of methanol can be added to significantly improve the cycle life of the aqueous zinc ion battery. In the present invention, due to the electronegativity of the lone pair of electrons carried by the P atom in the -P=O group in the tri-n-octylphosphine oxide, the side with the -P=O group in the molecule can be preferentially adsorbed on the surface of the zinc anode, and can be used as a zinc-philic nucleation site to induce uniform deposition of zinc ions. At the same time, a large number of -CH3 groups in the molecule are distributed on the outside to form a hydrophobic layer, thereby solving the inherent corrosion problem of the zinc anode. Therefore, during the cycle, a zinc-philic hydrophobic layer is formed on the surface of the zinc anode. At the same time, the additive can destroy the original hydrogen bond network, reduce the activity of water, and thus effectively solve the problems of hydrogen evolution, corrosion and dendrite growth.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: In a first aspect, the present invention provides an aqueous zinc ion battery electrolyte containing a tri-n-octylphosphine oxide additive, the components of which include the tri-n-octylphosphine oxide additive, methanol, zinc trifluoromethanesulfonate electrolyte and a solvent.

[0006] The tri-n-octylphosphine oxide additive has a molecular formula of C 24 H 51 PO, containing zinc-philic -P=O group and hydrophobic -CH3 group, has the following structural formula: Fig. 9 shown.

[0007] The solvent has a conductivity of 5 µS cm -1 of deionized water.

[0008] The concentration of the tri-n-octylphosphine oxide additive in the electrolyte is 25.6-76.8 mmol L -1 The volume ratio of methanol co-solvent to deionized water solvent was 1:1.

[0009] The water-soluble zinc salt is zinc trifluoromethanesulfonate, and the concentration of the electrolyte in the electrolyte is 3 mol L -1 .

[0010] In a second aspect, the present invention provides a method for preparing an aqueous zinc ion battery electrolyte containing a tri-n-octylphosphine oxide additive, comprising the following steps: Add a water-soluble zinc salt into deionized water, stir thoroughly until completely dissolved, and let stand to obtain a conventional electrolyte for aqueous zinc ion batteries.

[0011] A methanol co-solvent having the same volume as the solvent is added to a conventional electrolyte, and then the tri-n-octylphosphine oxide additive is added to the mixed solution of methanol and the conventional electrolyte, and stirred until the solution is clear to obtain the aqueous zinc ion battery electrolyte containing the tri-n-octylphosphine oxide additive.

[0012] In a third aspect, an application of an aqueous zinc ion battery additive electrolyte is provided, characterized in that: An aqueous zinc ion battery is constructed by using the aqueous zinc ion battery additive electrolyte.

[0013] The beneficial effects of the present invention are: The tri-n-octylphosphine oxide additive electrolyte of the aqueous zinc ion battery of the present invention can form a zinc-philic hydrophobic layer on the anode surface as a zinc-philic nucleation site to induce uniform deposition of zinc ions during the circulation process, and the external hydrophobic layer provides a hydrophobic environment for the anode, thereby solving the inherent corrosion problem of the zinc anode, and the additive can destroy the original hydrogen bond network, reduce the activity of water, and inhibit the hydrogen evolution reaction of the zinc anode. These ensure the stability and reversibility of the zinc anode during the circulation process, and improve the cycle life of the aqueous zinc ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is the contact angle measured before and after the commercial zinc foil is immersed in different electrolytes. Figure 1 a and a are the contact angles before and after immersion in the conventional electrolyte of Comparative Example 1, respectively. Figure 1 b and b respectively compare the contact angles before and after immersion in the electrolyte solution containing the tri-n-octylphosphine oxide additive described in Example 2.

[0015] Figure 2 It is the Fourier transform infrared spectra measured for the conventional electrolyte described in Example 1 and the electrolytes containing additives in Examples 1, 2 and 3.

[0016] Figure 3 The symmetrical battery assembled with commercial zinc foil and the electrolytes described in Example 2 and Comparative Examples 1 and 2 was -2 , 5 mAh cm -2 Voltage-time curve of constant current charge and discharge test under current density.

[0017] Figure 4 a is a symmetrical button cell assembled with the electrolyte described in Example 1 using commercial zinc foil at 1 mA cm -2 , 1 mAhcm -2 Scanning electron microscope image of the negative zinc sheet taken after disassembling the battery after 30 cycles at a current density of . Figure 4 b is a symmetrical button cell assembled with commercial zinc foil and the electrolyte described in Example 2 at 1 mA cm -2 , 1 mAh cm -2 Scanning electron microscope image of the negative zinc sheet taken after disassembling the battery after 30 cycles at a current density of .

[0018] Figure 5 It is the Tafel corrosion current curve of the zinc electrode in the conventional electrolyte described in Comparative Example 1 and the electrolyte added with zinc trifluoromethanesulfonate described in Example 2.

[0019] Figure 6 A symmetrical cell was formed by combining commercial zinc foil with the electrolytes added with zinc trifluoromethanesulfonate described in Examples 1, 2, and 3, the conventional electrolyte of Comparative Example 1, and the electrolyte added with only methanol as a co-solvent of Comparative Example 2 to conduct a chronoamperometry test (CA).

[0020] Figure 7 The coulombic efficiency comparison curve is obtained by testing half-cells assembled with commercial zinc foil as the negative electrode and commercial copper foil as the positive electrode, respectively, with the electrolyte added with zinc trifluoromethanesulfonate in Example 2, the conventional electrolyte in Comparative Example 1, and the electrolyte only with methanol co-solvent added in Comparative Example 2.

[0021] Figure 8 The figure is a comparison chart of the discharge specific capacity and charge-discharge efficiency of the full battery cycle test assembled with the commercial zinc foil as the negative electrode and I2 as the positive electrode, respectively, and the electrolyte with zinc trifluoromethanesulfonate added as described in Example 2 and the conventional electrolyte of Comparative Example 1.

[0022] Fig. 9 It is the structural formula of the additive tri-n-octylphosphine oxide. DETAILED DESCRIPTION

[0023] Example 1 The preparation process of the aqueous zinc ion battery tri-n-octylphosphine oxide additive electrolyte of the present invention is as follows: This embodiment provides an aqueous zinc ion battery electrolyte containing a tri-n-octylphosphine oxide additive, wherein the electrolyte includes the tri-n-octylphosphine oxide additive, a methanol cosolvent, a water-soluble zinc trifluoromethanesulfonate salt (Zn(OTF)2) electrolyte, and a deionized water solvent.

[0024] In Example 1, the preparation method of the aqueous zinc ion battery trifluoromethanesulfonate additive electrolyte is: wherein the concentration of zinc trifluoromethanesulfonate is 3 mol L -1 The volume ratio of methanol cosolvent and deionized water solvent was 1:1, and the concentration of tri-n-octylphosphine oxide was 25.6 mmol L -1 , weigh each component, and stir until the solution is clear to obtain the electrolyte.

[0025] Example 2 In Example 2, the preparation method of the aqueous zinc ion battery trifluoromethanesulfonate additive electrolyte is: wherein the concentration of zinc trifluoromethanesulfonate is 3 mol L -1 The volume ratio of methanol cosolvent and deionized water solvent was 1:1, and the concentration of tri-n-octylphosphine oxide was 51.2 mmol L -1 , weigh each component, and stir until the solution is clear to obtain the electrolyte.

[0026] Example 3 In Example 3, the preparation method of the aqueous zinc ion battery trifluoromethanesulfonate additive electrolyte is: wherein the concentration of zinc trifluoromethanesulfonate is 3 mol L -1 The volume ratio of methanol cosolvent and deionized water solvent was 1:1, and the concentration of tri-n-octylphosphine oxide was 76.8 mmol L -1 , weigh each component, and stir until the solution is clear to obtain the electrolyte.

[0027] Comparative Example 1 In order to compare the effects of the aqueous zinc ion battery tri-n-octylphosphine oxide additive electrolyte of the present invention and a conventional electrolyte without additives on inhibiting zinc dendrites and other electrochemical properties, a conventional electrolyte was prepared, which specifically consisted of zinc trifluoromethanesulfonate and deionized water solvent.

[0028] The preparation method is as follows: deionized water is used as the solvent, and 3 mol L -1 A zinc trifluoromethanesulfonate electrolyte was prepared with a volume molar concentration of and uniformly stirred until completely dissolved to obtain a conventional electrolyte prepared in Comparative Example 1.

[0029] Comparative Example 2 In order to compare the effects of the aqueous zinc ion battery tri-n-octylphosphine oxide additive electrolyte of the present invention on inhibiting zinc dendrites and other electrochemical properties with the electrolyte to which only methanol co-solvent is added, an electrolyte to which only methanol co-solvent is added is prepared, and its specific composition is zinc trifluoromethanesulfonate, methanol co-solvent and deionized water solvent.

[0030] The preparation method is as follows: deionized water is used as the solvent, and 3 mol L -1 A zinc trifluoromethanesulfonate electrolyte was prepared with a volume molar concentration of, and a methanol co-solvent having an equal volume to deionized water was added, and the mixture was stirred evenly until completely dissolved to obtain the electrolyte prepared in Comparative Example 2 with only the methanol co-solvent added.

[0031] Performance and results analysis The electrolyte containing tri-n-octylphosphine oxide additive in Example 2 and the conventional electrolyte in Comparative Example 1 were dropped on the surface of commercial zinc foil to measure their contact angles. The commercial zinc foil was then soaked in the electrolyte containing tri-n-octylphosphine oxide additive in Example 2 and the conventional electrolyte in Comparative Example 1 for three days, then taken out, rinsed and dried. The corresponding electrolytes were then dropped on the surface to measure their contact angles. Figure 1 It can be seen from a that the contact angle between the conventional electrolyte and the commercial zinc foil in Comparative Example 1 is significantly reduced after the foil is immersed, indicating that the conventional electrolyte has limited anti-corrosion ability against the zinc anode. Figure 1 The contact angle between the electrolyte containing tri-n-octylphosphine oxide additive and the commercial zinc foil in Example 2 in b has increased significantly after immersion. This can indicate that the electrolyte containing tri-n-octylphosphine oxide additive forms a hydrophobic layer on the surface of the zinc foil, which can effectively increase the contact angle between the electrolyte and the zinc foil, thereby inhibiting the corrosion of the zinc anode, indicating its protective effect on the zinc anode.

[0032] The Fourier transform infrared spectra of the conventional electrolyte in Comparative Example 1 and the electrolytes containing tri-n-octylphosphine oxide additive in Examples 1, 2, and 3 were measured respectively, and it can be found that the peaks at 3100-3400 cm -1The HO stretching vibration shifts to a higher wavenumber, indicating that the coordination interaction between water and zinc trifluoromethanesulfonate weakens the hydrogen bond network between water molecules and can effectively inhibit the evolution of hydrogen gas.

[0033] A symmetrical battery was assembled with commercial zinc foil as the negative electrode, the electrolyte containing tri-n-octylphosphine oxide additive in Example 2, the conventional electrolyte in Comparative Example 1, and the electrolyte containing methanol cosolvent in Comparative Example 2, and a constant current charge and discharge test was performed. The test method was to test the electrolyte at 5 mA cm -2 , 5mAh cm -2 The time-voltage curve of the constant current charge-discharge test is as follows: Figure 2 As shown in the figure, the symmetrical battery assembled using the electrolyte containing tri-n-octylphosphine oxide additive in Example 2 of the present invention exhibits an extremely long cycle life. -2 The current density can be stably cycled for more than 4000 h; while the 3 mol L -1 The conventional zinc trifluoromethanesulfonate electrolyte and the electrolyte with methanol as a co-solvent showed poor cycle life and stability. -2 The cycle life and stability of the symmetrical battery made of the electrolyte containing tri-n-octylphosphine oxide additive obtained in Example 2 of the present invention are far lower than those of the symmetrical battery made of the electrolyte containing tri-n-octylphosphine oxide additive obtained in Example 2 of the present invention.

[0034] The tri-n-octylphosphine oxide additive electrolyte in Example 2 of the present invention and the conventional electrolyte in Comparative Example 1 were respectively applied to zinc-zinc symmetrical button cells. -2 The charge and discharge cycle was carried out at a current density of 2 hours. After 30 cycles, the battery was disassembled and the dendrite growth on the surface of the zinc sheet was observed using a scanning electron microscope. The results of the scanning electron microscope observation are shown in the figure. Figure 4 As shown, Figure 4 a is a scanning electron microscope image of a zinc sheet using conventional electrolyte circulation in a comparative example, Figure 4 b is a scanning electron microscope image of a zinc sheet using the electrolyte with tri-n-octylphosphine oxide additive in Example 2. The results show that the zinc surface using the electrolyte with tri-n-octylphosphine oxide additive of the present invention is flat and has no obvious dendrites, while the zinc surface using the conventional additive electrolyte in Comparative Example 1 forms serious and disorderly distributed flaky zinc dendrites, and these protrusions generated by the "tip effect" further lead to uneven nucleation of zinc ions, resulting in rapid growth of dendrites and aggravated surface side reactions.

[0035] The commercial zinc foil was subjected to Tafel corrosion current curve test in the electrolyte containing tri-n-octylphosphine oxide additive in Example 2 and the conventional electrolyte in Comparative Example 1. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the corrosion current of the electrolyte containing tri-n-octylphosphine oxide additive is significantly reduced, indicating its protective effect on the zinc negative electrode.

[0036] In order to explore the effect of different electrolytes on the diffusion of zinc ions, we used commercial zinc foil to assemble a zinc-zinc symmetric battery with different electrolytes for the measurement of it curves. Figure 6 It can be seen from the results that the current density of the conventional additive electrolyte battery in Comparative Example 1 continues to increase rapidly, while the current density of the tri-n-octylphosphine oxide additive electrolyte batteries in Examples 1, 2, and 3 of the present invention tends to be stable after a short nucleation process of 10 seconds, and a stable and continuous three-dimensional diffusion process occurs. The stable low current density means that the zinc deposition is uniform, and the fast ion transfer power will reduce the diffusion polarization, thereby regulating the zinc deposition.

[0037] The coulombic efficiency of the half-cells assembled with commercial zinc foil as the negative electrode and commercial copper foil as the positive electrode and the electrolyte with tri-n-octylphosphine oxide additive in Example 2, the conventional electrolyte in Comparative Examples 1 and 2, and the electrolyte with only methanol as the cosolvent were tested. The test method was as follows: -2 After discharging for 1h at a current density of , it is charged to 0.5V and then cycled. The Coulomb efficiency test comparison curve is as follows Figure 7 As shown. Figure 7 It can be seen that the zinc-copper half-cell assembled with the electrolyte containing tri-n-octylphosphine oxide additive showed more stable cycling performance at 2 mA cm -2 The Zn-Cu half-cell assembled with conventional electrolyte and methanol as co-solvent can be cycled stably for about 500 times at a current density of 2 mA cm -2 The stable cycle times at current density of less than 20 and 40 times respectively showed extremely unstable curve fluctuations, which means that a short circuit occurred inside the battery in a very short time.

[0038] The charge and discharge capacity of the full battery assembled with commercial zinc foil as the negative electrode and I2 as the positive electrode was tested and compared with the electrolyte added with tri-n-octylphosphine oxide additive in Example 2 and the conventional electrolyte in Comparative Example 1. The test method was as follows: -1 The battery was discharged to 0.5 V at a current density of , and then charged to 1.6 V, and then cycled. The comparison of the discharge capacity and charge-discharge efficiency of the full battery cycle test is shown in the figure below. Figure 8 As shown. Figure 8It can be seen that the full battery with the electrolyte containing tri-n-octylphosphine oxide additive still has a high capacity retention after 4000 cycles, while the full battery using conventional electrolyte shows obvious capacity decay after 100 cycles, and the final capacity retention rate is only about 20%.

[0039] As described above, Example 2 is a more suitable implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A preparation and application of an aqueous zinc ion battery electrolyte containing a trace amount of tri-n-octylphosphine oxide additive, characterized in that: The following steps are involved: Step 1: adding soluble zinc trifluoromethanesulfonate salt to deionized water to dissolve to obtain a conventional aqueous zinc salt electrolyte; Step 2: adding methanol of the same volume as deionized water, stirring to fully mix, and standing to obtain an electrolyte solution to which only methanol co-solvent is added; Step 3: Add tri-n-octylphosphine oxide additive to the electrolyte to which methanol co-solvent is added, continue stirring until the solution is completely transparent, and after standing, obtain an aqueous zinc ion battery electrolyte containing tri-n-octylphosphine oxide additive; wherein the concentration of soluble zinc trifluoromethanesulfonic acid salt is 3 mol L -1 The concentration of tri-n-octylphosphine oxide additive was 25.6-76.8 mmol L -1 , molecular formula is C 24 H 51 OP, whose structural formula is shown in FIG9 .

2. The method for preparing an electrolyte containing a tri-n-octylphosphine oxide additive according to claim 1, characterized in that: The water-soluble zinc salt is zinc trifluoromethanesulfonate.

3. A battery comprising an aqueous zinc ion battery electrolyte prepared by the preparation method described in claims 1-2.

4. The battery according to claim 3, characterized in that The battery is a symmetrical battery composed of 100µm thick commercial zinc foil, glass fiber separator and aqueous zinc ion battery electrolyte; or a half-cell consisting of a 100µm thick commercial zinc foil, a commercial copper foil and an aqueous zinc ion battery electrolyte; Or an aqueous zinc ion full battery composed of a 100µm thick commercial zinc foil as the negative electrode, a composite material of iodine and activated carbon as the positive electrode, and an aqueous zinc ion battery electrolyte as the electrolyte.

5. The battery according to claim 3, characterized in that The working current density is 1~5 mA cm -2 .